Development of Chrysomya megacephala at constant temperatures within its colony range in Yangtze River Delta region of China - Yingna Zhang; Yu Wang; Lijun Yang; Luyang Tao; Jiangfeng Wang (Oxford University Press, 2018)
Chrysomya megacephala (Fabricius, 1794) is the most abundant and predominant species which arrives and colonizes a cadaver first in most parts of China. Therefore, its growth and development patterns have great implications in the estimation of the minimum postmortem interval (PMImin). In this study, C. megacephala was collected from the Yangtze River Delta region and reared at seven constant temperatures ranging from 16 °C to 34 °C. The developmental duration and accumulated degree hours, larval body length and morphological changes of C. megacephala were examined. Furthermore, we constructed three developmental models, isomorphen diagram, isomegalen diagram and thermal summation model, which can be used for estimating PMImin. The developmental durations of C. megacephala at 16 °C, 19 °C, 22 °C, 25 °C, 28 °C, 31 °C and 34 °C are (794.8 ± 14.7), (533.2 ± 10.1), (377.8 ± 16.8), (280.8 ± 15.1), (218.9 ± 8.5), (190.8 ± 10.1) and (171.8 ± 6.8) h, respectively. The developmental threshold temperature D0 is (11.41 ± 0.32) °C, and the thermal summation constant K is (3 418.7 ± 137.0) degree hours. Regression analysis was conducted to obtain equations of the variation in larval body length with time after hatching, and variation in time after hatching with body length. Moreover, our study divides the intra-puparial morphological changes of C. megacephala into 11 sub-stages, and provides the time range experienced by each sub-stage. The results of this study provide fundamental development data for the use of C. megacephala in PMImin estimations.